La relation paysans-paysages entre discours et savoirs - Amandine Saget (Projets de Paysage)
Associating farmers and landscapes is commonplace these days. However, there is too often an implicit perception of this relationship which leads to a distanced perspective, whether it be in scientific research or in action. Such a perspective separates the everyday life of farmers from the physical creation of landscapes. More specifically, active approaches based on this relationship tend to disregard the ordinary experiences of the farmers. Paradoxically, although these approaches are based on this relationship they actually seem to disregard the capacity of farmers to act on the landscape from day to day. This article invites the reader to learn about the initial theoretical and methodological principles to gain an understanding of this relationship and engage in continuous action without disregarding the farmers’ experiences and how these experiences relate to the landscape. To achieve this, a period of participative observation was conducted on a dairy farm in the Basque hinterland. It served as a basis for the gradual construction of a theoretical framework and of a set of observation tools which, while not yet fully tested, show promise in terms of practical action.